Purchasing Power Parities and Real Expenditures of World Economics : A Comprehensive Report of the 2011 International Comparison Program - World Bank (Washington, DC, 2014)
The International Comparison Program (ICP) is a large and highly complex worldwide statistical program conducted under the charter of the United Nations Statistical Commission (UNSC). The ICP is designed to provide globally comparable economic aggregates in national accounts that can be used by individual researchers, analysts, and policy makers at the national and international levels and by international organizations such as the European Union, International Monetary Fund, Organization for Economic Co-operation and Development (OECD), United Nations, and World Bank. Over its lifetime, the ICP has become the principal source of data on the purchasing power parities (PPPs) of currencies, measures of real per capita income, and measures of real gross domestic product (GDP) and its main components from the expenditure side, including private consumption, government expenditures, and gross fixed capital formation. Indeed, since its inception in 1970, successive rounds of the ICP have produced valuable data for international economic analyses of economic growth and the catch-up and convergence of incomes among nations; productivity levels and trends; analyses of systematic patterns in national price levels and trends; construction of the Human Development Index by the United Nations; measures of regional and global inequality in incomes and consumption; and estimates of the incidence of absolute poverty using World Bank developed yardsticks such as the US$1 a day and $2 a day poverty lines.